Coordinating R&D efforts for quality improvement along a supply chain - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
The optimal design of two-part tariffs is investigated in a dynamic model where two firms belonging to the same supply chain invest in R&D activities to increase the quality of the final product. It is shown that the replication of the vertically integrated monopolist's performance can be attained using a TPT in which the fee is a linear function of either the upstream R&D effort or product quality itself. The possibility of relying on R&D figures appearing in the upstream firm's balance sheet is desirable as quality enhancement might not be observable or verifiable.
Keywords: C73; L12; O31; 330